2019
DOI: 10.7554/elife.48958
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific regulation of stem cell-driven regeneration in tapeworms

Abstract: Tapeworms grow at rates rivaling the fastest-growing metazoan tissues. To propagate they shed large parts of their body; to replace these lost tissues they regenerate proglottids (segments) as part of normal homeostasis. Their remarkable growth and regeneration are fueled by adult somatic stem cells that have yet to be characterized molecularly. Using the rat intestinal tapeworm, Hymenolepis diminuta, we find that regenerative potential is regionally limited to the neck, where head-dependent extrinsic signals … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…In flatworms, differentiated cells do not proliferate; thus, genes regulated in a cell cycle-dependent manner, such as histone 2b ( h2b ), can be used as generic stem cell markers ( 6 , 15 17 ). Using h2b as a marker of these cells in cercariae ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In flatworms, differentiated cells do not proliferate; thus, genes regulated in a cell cycle-dependent manner, such as histone 2b ( h2b ), can be used as generic stem cell markers ( 6 , 15 17 ). Using h2b as a marker of these cells in cercariae ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several species of Platyhelminthes and Acoelomorpha (acoel flatworms) exhibit extensive regenerative capacities, up to whole-body regeneration [110][111][112][113][114]. This capacity requires a group of ASCs called neoblasts [115][116][117] that are located within the parenchymal tissue of many freeliving (e.g., [111,118]) and parasitic flatworms [119].…”
Section: Platyhelminthes and Acoelomorphamentioning
confidence: 99%
“…In well-studied species, such as Schmidtea mediterranea, the neoblasts constitute up to one-third of the animal's cells [120] and are known to be the only proliferating cells in the adult body. Regeneration properties have been thoroughly examined in a few species: the Platyhelminthes S. mediterranea [111,121], Dugesia japonica [122], the tapeworm Hymenolepis diminuta [114], and the acoels Isodiametra pulchra [26] and Hofstenia miamia [123,124]. Early experiments demonstrated that all new somatic cells emerging during tissue maintenance, as well as during regeneration, originated from neoblasts [111,125].…”
Section: Platyhelminthes and Acoelomorphamentioning
confidence: 99%
“…For instance, proglottids lack the set of characters that has been used to define segments (see Scholtz, 2002Scholtz, , 2010Scholtz, , 2020c. Furthermore, proglottids do not form by a combination of a pre-anal proliferation zone and an anteroposterior differentiation of segments, but rather by stem cells that form a growth zone in the neck area behind the anterior scolex; the differentiation follows a posteroanterior gradient (Koziol et al, 2016;Olson, 2008;Rozario et al, 2019). Likewise, the formation of the cuticular annuli in nematodes follows a different pathway compared with annelids and arthropods.…”
Section: A Common Principle Underlying Seriality In Bilaterians?mentioning
confidence: 99%